Effort to Instill Attitudes in Social Studies Learning in Elementary School - Sartika, Wawa; Daryanto, Silva Aulia Putri; Pebriyani, Ghesti Aulia; Aulia, Salma Nur; Kurnia, Budi (Education Achievement: Journal of Science and Research, 2025)
The cultivation of attitudes in social studies (IPS) learning at the elementary school level aims to shape students into individuals with strong social character, such as discipline, Tolerance, responsibility, and cooperation. Social studies learning provides opportunities for teacher to integrate social values into lesson content through various strategies and methods. Commonly used strategies include affective approaches, habituation, role modeling, group discussion, project based learning, and role playing simulations. Teachers serve as role models by demonstrating positive attitudes bpth inside and outside the classroom. Additionally, the use of relevant learning media and rubic based evaluations helps monitor students attitude development. This process is also supported by the preparation of lesson plans (RPP) that include specific objectives related to instilling social values. Challenges in implementation include a Lack of support from families and the community, as well as varying level of student awareness regarding the importance of social values. The outcomes of applying these strategies show a positive impact on shaping students social attitudees, such as honesty, politeness, tolerance, and responsibility. Therefore, social studies learning funtions not only as a mean of knowledge transfer but also as a medium for character building that contributes to social life.